SIMBIOSIS MUTUALISME MIKROALGE Chlorella sp DENGAN BAKTERI PENGURAI B-DECO3 DALAM MENURUNKAN KADAR POLUTAN LIMBAH CAIR SAGU - Pasaribu, Jekson; Restuhadi, Fajar; Zalfiatri, Yelmira (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Liquid waste containing high levels of pollutants sago, so need to do processing of biological, physical and chemical.This research was to study the symbiotic system of a complex microorganisms contained in B-DECO3 as a decomposer agent, with the addition of photosynthetic microoalgae Chlorella sp as an oxygen producer in reducing organic loads of sago milling effluent. The method used in the experiment with completely randomized design (CRD) comprised of 5 treatments and 3 replications. The treatments were concentration variations of microorganisms B-DECO3 (0, 0.27, 0.55, 0.82 and 1.09 per cent v/v, respectively) with 800 ml/L (6.6 x 106 cell/ml) microalgae Chlorella sp. added up with waste sago milling effluent 1 liters of the liquid. Observations were made on day 0 and day to-7, except for the parameters pH, DO, and an abundance of cells is done every day. Data were analyzed statistically using Analysis of Variance (ANOVA) and Duncanâ€™s Multiple Range Test (DNMRT) at 5% level. The results showed the role of symbiotic mutualism can reduce levels of pollutants wastewater sago. The best treatment is the addition of bacterial decomposition P4 B-DECO3Chlorella sp 20 ml and 800 ml (abundance of 6.6 x 106 cells / mL). P4 treatment lowers the value of COD 90.29%, 82.74% BOD, TSS 84.52%, 82.85% Nitrate and Phosphate 98.66%, and increasing the pH value of 97.56%, 73.82% DO, and cell abundance 72.44% Chlorella sp.Â Â Keywords: B-DECO3 microorganisms, Microalgae Chlorella sp, liquid waste sago